SISTEM PERINGATAN DINI AKAN BAHAYA KEBAKARAN - Wiweko, Wiweko; Suharto, Hang (TESLA Jurnal Teknik Elektro UNTAR, 2008)
Fire disaster is one from many other disasters that very dangerous because not only it’s took heavy financial and material loss, but also often takes lives. For this reason, it needs the system which can give early warning not only to the people around the building but also to the building owner. This system must also work to delay fire spreading. This paper discuss the designing and implementation of early warning system to help minimize loss from fire disaster.